Myxomatous Degeneration of Atrioventricular Valves in a Crab-eating fox (Cerdocyon thous) - Echodopplercardiography Diagnosis - Santos, Juliana Godoy; Franco, Ellen Ronara de Jesus; Fliegner, Eduarda Bagini; Borba, Jullia de Pinho; Ribeiro, Marlon; Colodel, Edson Moleta; Morgado, Thais Oliveira; Néspoli, Pedro Eduardo Brandini (Acta Scientiae Veterinariae, 2022)
Background: The myxomatosis degeneration is a degenerative cardiac valve disease, with a higher incidence in male and senile canids. The diagnosis is made by a doppler echocardiography exam. Although there are few reports on the occurrence of cardiopathies in wild dogs (Cerdocyon thous), some studies on their cardiological parameters can be found. Considering this, and knowing that the cardiopathies in wild canids are common post mortem findings, the objective of this study is to describe the echocardiography diagnosis of a case of myxomatous degeneration of the atrioventricular valves in 1 wild dog (Cerdocyon thous) living in captivity. Case: It was treated at the Diagnostic Imaging Department of the Veterinary Hospital of the Federal University of Mato Grosso (HOVET-UFMT), 1 wild dog (C. thous), male, living in captivity with approximately 10-year-old, directed by the Center of Medicine and Research in Wild Animals of Cuiabá, to perform echocardiography exam. The patient was submitted to anesthesia for proper examination, which was used Esaote® machine model MyLabFive VET with sector scan transducer (4.0 -7.5 MHz). The longitudinal, transverse and apical scan planes were obtained through left and right parasternal windows. The evaluation of M mode exposed ejection fraction and shortening increased, of 81% and 47%, respectively, however it showed no increase in systolic and diastolic values of left ventricle, nor in right cavities on subjective evaluation. The relation between the left atrium (LA) and the aorta (Ao) remained normal, at 1.2 mm, with dimensions of 13.4 mm from the AO and 16.3 mm from LA, compatible with species parameters or domestic canines. The atrioventricular valves showed thickening and irregularities in their cusps, with great intensity in the left atrioventricular valve (LAV). The Doppler mode analysis revealed a turbulent systolic flow into the left atrium and right atrium, constituting transvalvular LAV and right atrioventricular valve- (RAV) regurgitation, both observed through the blood flow in colored Doppler and measured through the reflux velocity of 4.02 m/s of LAV and 2.17 m/s of RAV by the continuous Doppler, showing insufficiency of intense degree of LAV and moderate degree of RAV, no evidence of pulmonary hypertension. On the other hand, the relation between wave E and wave A (E/A) was 1.0, with increased transvalvular velocities and values of 0.95 m/s for wave E and A. The isovolumetric mitral relaxation time was approximately 76 m/s. The value of the pressure derivative (dp) in relation to time (dt) dp/dt measured from the LAV reflux was 1257 mmHg, within the limit considered normal for canines. Four months after the diagnosis, the patient died due to complications of chronic renal failure. Discussion: Despite being a commonly diagnosed pathology in domestic canids, the myxomatous degeneration of atrioventricular valves is still little reported in wild canids. The evaluation of the results showed that although there was severe LAV regurgitation, there was no hypertrophy or compensatory dilation of the left cavities. However, there was a compensatory increase in the shortening fraction together with the ventricular relaxation deficit. The diagnosis of this condition in Cerdocyon thous demonstrates that the pathology can affect animals of advanced age and that its incidence needs to be determined in these captive species, in order to understand the real impact of this disease in these populations. Keywords: cardiopathies, cardiac valve disease, degenerative disease, cardiological parameters, wild dog. Título: Degeneração mixomatosa das válvulas atrioventriculares em cachorro-do-mato (Cerdocyon thous) - diagnóstico ecocardiográfico Descritores: cardiopatias, doença valvular cardíaca, doença degenerativa, parâmetros cardiológicos, canídeo selvagem.